Antibiotic Susceptibility Pattern of Bacterial Isolates from Soft Tissues Infection among Patients Visiting Birendra Military Hospital, Chhauni, Kathmandu - Giri, Kushaalta; Gurung, Sharada; Subedi, Simrika; Singh, Alina; Adhikari, Nabaraj (Tribhuvan University Journal of Microbiology, 2019)
Objectives: To determine the rate of soft tissues infection and perform antibiotic pattern susceptibility test of bacterial pathogens isolated from soft tissue infected patients visiting Shree Birendra Hospital, Kathmandu, Nepal. Methods: A total of 380 wound specimens (open and closed) including pus and wound swabs were processed in the laboratory of Birendra Military Hospital, Chhauni from August to November 2018. The specimens were cultured on Blood Agar blood agar and Mac-Conkey agar and incubated at 37°C for 24 hrs. Antibiotic Susceptibility Test was performed by using modified Kirby-Bauer disc diffusion method. Thus, multidrug resistant (MDR) bacteria and methicillin resistant Staphylococcus aureus (MRSA) were differentiated. Results: Out of 380 bacterial isolates, 86(43.21%) were gram positive and 113(56.78%) were gram negative bacteria. Among all the gram-positive isolates 43(53.09%) were found to be MRSA. Similarly, 62(54.86%) were found to be MDR among the gram-negative bacteria. Gentamicin and Amikacin were found to be the most effective drug though the resistance pattern is not homogenous against all isolates. Conclusion: Antibiotic susceptibility pattern of all bacterial isolates showed that, Gentamycin, Amikacin, Levofloxacin, Piperacillin/ Tazobactam, Doxycycline was the effective drug for Gram-negative bacteria and Amikacin, Teicoplanin, Linezolid, Doxycycline, Gentamycin and Azithromycin was the most effective drug for Gram-positive organisms. Thus it can be concluded that these antibiotics may be used for the empirical treatment of soft tissues infection.